System Security Awareness Planning Model Using The Octave Method Approach - Zaied Saad Shouran; Nur Rokhman; Tri Kuntoro Priyambodo (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2019)
Awareness of the security of information systems is an important thing to note. In this study, we will discuss planning models of awareness about information system security using Octave models or methods. The analytical method used is qualitative descriptive analysis. The results of the study show that the Octave model can increase awareness about the importance of security in an information system and companies that implement it will be able to improve their performance in the future.